Ten commitments revisited : securing Australia's future environment - Lindenmayer, David; Dovers, Stephen; Morton, Steve (CSIRO Publishing, 2014)
What are the 10 key issues that must be addressed urgently to improve Australia's environment? In this follow up to the highly successful book Ten Commitments: Reshaping the Lucky Country'sEnvironment, Australia's leading environmental thinkers have written provocative chapters on what must be done to tackle Australia's environmental problems - in terms of policies, on-ground actions and research.Chapters are grouped into ecosystems, sectors and cross-cutting themes. Topics include: deserts, rangelands, temperate eucalypt woodlands, tropical savanna landscapes, urban settlements, forestry management, tropical and temperate marine ecosystems, tropical rainforests, alpine ecosystems, freshwater ecosystems, coasts, islands, soils, fisheries, agriculture, mining, grazing, tourism, industry and manufacturing,protected areas, Indigenous land and sea management, climate change, water, biodiversity, population, human health, fire, energy and more. Ten Commitments Revisited is a 'must read' for politicians, policy makers, decision makers, practitioners and others with an interest in Australia's environment.